EFFECT DISCUSSION INSTITUTION MANAGEMENT ON THE ACHIEVEMENT OF WOMEN STUDENTS MADRASAH AN-NAWAWI PURWOREJO INDONESIA - Muhlil Musolin; Waluyo Sudarmaji; Rosa Sugesti Hadi (IJGIE (International Journal of Graduate of Islamic Education), 2022)
This study aims to analyze how much influence Deliberative Management has on the Competence of Students at the Madrasah Diniyyah Banat An-Nawawi Deliberation Council. Deliberative management is the art of planning, organizing, implementing, and assessing deliberation activities where a student gathers together to discuss a problem given by a cleric or ustadz / ustadzah or senior santri. There is an organization that manages the deliberation, namely the Madrasah Diniyyah Banat An-Nawawi Deliberation Council. The achievement of the expected competencies is the competence of students, namely, critical thinking and problem solving, communication skills, and the ability to work together. In this study, the authors used cluster random sampling technique with a sample of 74 respondents. It can also be seen that the results of tcount (319.058)> t table (1.992997), which means that Ha is accepted and there is a significant influence between Deliberation Management on The Competence Achievement of Students in The Madrasah Diniyyah Banat An-Nawawi Assembly. Based on the results of the research that has been carried out, it can be concluded that there is a significant influence between deliberation management on the achievement of student competence at the Madrasah Diniyyah Banat An-Nawawi Deliberative Council. From these results, it shows that the coefficient of determination is 25.61%, and the remaining 74.39% is influenced by other factors not mentioned in the variables of this study, such as environmental factors, students' daily lives, and others.